The BAMSE project - The BAMSE projekt 4 years - Wickman, Magnus; Pershagen, Göran; Kull, Inger; Melén, Erik; Bergström, Anna (Karolinska Institutet, 2012)
Both heredity and environmental factors influence childrens' risk for developing respiratory and allergy related diseases, but how these factors influence the age of onset and the prognosis is little studied. It is also unknown which factors determine whether these diseases disappear in the childhood years, if they remain mild or worsen. An integrated database where lifestyle and allergic diseases are studied from birth through adolescence is lacking both nationally and internationally.

From 1994 to 1996 a little more than 4,000 children were borne in certain pre-selected areas of Stockholm County. They have been followed repeatedly with questionnaires and surveys (at 0, 1, 2, 4, 8 and 12 years of age) as part of the so-called BAMSE project. In the last follow-up the response rate was 82% compared to baseline.

Now, when the youths have reached the age 16 years, a resource-intensive data collection has started, including studies of weight, height, blood pressure, lung function tests, patch tests and blood tests (complete blood count, allergy levels and genetics, and nasal lavage). A larger database of more than 6000 variables containing all the information gathered has gradually been built up. Extensive national and international research cooperation around environmental factors and genetics in relation to the development of pulmonary and allergic diseases has been established within the project.

By using the collected data material the development of allergic diseases has been described as well as risk factors for allergic diseases and the impact on quality of life of such diseases. More than 70 scientific articles have been published and 16 doctoral dissertations and licentiate thesis has been presented. Extensive efforts to develop the database are ongoing through entering and evaluating the collected data, work with descriptions of individual and composite variables that are used by the various research groups, and through developing the epidemiological and statistical analysis techniques. With help from epidemiology assistants and statisticians a high quality of the data used by different research groups is ensured.

New opportunities for research: More than 30 senior researchers at KI, as well as nationally and internationally outside KI works within the project. The project is part of a European cooperation in which a significant number of cohorts are included in order to obtain sufficient statistical power. Data on more than 30 000 children are included in the European database where BAMSE is contributing with data on 4000 children. Several areas can be researched, but the main emphasis will be on respiratory and allergic diseases, environmental factors and genetics. Great efforts are made for the database to become known and available to researchers. The BAMSE database structure is already available online at three different sites.

Importance of study: With its population-based recruitment, repeated follow-ups with the collection of biological material throughout childhood and into adolescence, little loss, more than 6000 variables, a European cooperation and the development of a common database of more than 30 000 children, there is an excellent opportunity to cutting-edge research aimed at preventing pulmonary and allergic diseases and to reduce the burden on those already affected.

Purpose:

To better understand how factors such as environment and lifestyle affect the risk of allergic disease in childhood.

Blood samples collected from 2965 participants

Både ärftliga och miljörelaterade faktorer påverkar risken att barn insjuknar i lung- och allergirelaterade sjukdomar, men hur dessa faktorer påverkar debutålder och prognos är föga studerat. Likaså är det okänt vilka faktorer som avgör om dessa sjukdomar går tillbaka under barnaåren, om de förblir av lindrig art eller förvärras. En sammanhållen databas där livsstil och allergisjukdom studeras från födseln till och med tonåren saknas både nationellt och internationellt.

Infrastrukturens användning: från 1994 till 1996 föddes drygt 4000 barn i vissa på förhand utvalda områden i Stockholms län. Dessa har följts med upprepade frågeformulär och undersökningar inom ramen för det s.k. BAMSE-projektet (0, 1, 2, 4, 8 och 12 år). Vid den senaste uppföljningen var svarsfrekvensen 82% jämfört med studiestart.

Nu när ungdomarna är 16 år pågår en mycket resurskrävande datainsamling inkluderande en rad undersökningar: vikt, längd, blodtryck, olika lungfunktionstester, lapptest samt blodprov (blodstatus, allerginivåer och genetik och nässköljning). En större databas på mer än 6000 variabler innehållande all insamlad information har succesivt byggts upp. Ett omfattande nationellt och internationellt forskningssamarbete är etablerat kring miljö och genetik i relation till utveckling av lung- och allergisjukdomar inom ramen för projektet.

Med data från det insamlade materialet har utvecklingen av allergisjukdomar beskrivits liksom riskfaktorer för allergisjukdomar samt konsekvenser på livskvalitén av sådana sjukdomar. Mer än 70 vetenskapliga artiklar har publicerats, 16 doktorsavhandlingar och en licentiatavhandling har lagts fram. Fortlöpande sker ett omfattande arbete med att utveckla databasen genom att lägga in och utvärdera insamlade data, arbeta med beskrivningar av enskilda och sammansatta variabler som används av de olika forskargrupperna, samt utveckla den epidemiologiskt/statistiska analystekniken. Med hjälp av epidemiologassistenter och statistiker säkerställs en hög kvalitet i de datasett som används av olika forskargrupper.

Nya möjligheter till forskning: Mer än 30 seniora forskare inom KI, nationellt utanför KI samt internationellt samarbetar med projektet. Projektet ingår i europasamarbete där ett flertal kohorter ingår för att erhålla tillräcklig statistisk teststyrka. Data på mer än 30 000 barn finns i den gemensamma europeiska databasen där BAMSE således bidrar med data på 4000 barn. Ett flertal områden kan beforskas, men huvudvikt kommer att ligga på lung- och allergisjukdomar, miljö och genetik. Stora ansträngningar görs för att databasen ska bli allmänt känd och tillgänglig för forskare. BAMSE-databasens struktur finns bl.a. tillgänglig via internet på tre sajter.

Betydelse: Genom sin populationsbaserade rekrytering, upprepade uppföljningar med insamlande av biologiskt material under hela barndomen och upp i tonåren, litet bortfall, mer än 6 000 variabler, europeiskt samarbete och uppbyggnad av gemensam databas på mer än 30 000 barn, så föreligger det utmärkta möjligheter till världsledande forskning med syfte att förebygga lung- och allergisjukdomar samt att minska bördan för redan drabbade.

Syfte:

Att bättre förstå hur faktorer som miljö och livsstil påverkar risken för allergisjukdom under uppväxten.

Blodprov från 2965 deltagare.
BAMSE projektet 4 år
Keywords: Blood Pressure; Blodtryck; Blood Specimen Collection; Blodprovstagning; Life Style; Livsstil; Longitudinal Studies; Longitudinella studier; Prospective Studies; Prospektiva studier; Socioeconomic Factors; Socioekonomiska faktorer; Allergens; Allergener; Allergy and Immunology; Allergi och immunologi; Respiratory Function Tests; Respiratoriska funktionstester; Respiratory Sounds; Andningsljud; Asthma; Astma; Child; Barn; Eczema; Eksem; Genetics; Genetik; Body Height; Kroppslängd; Body Weight; Kroppsvikt; Patch Tests; Lapptester; Food Hypersensitivity; Livsmedelsöverkänslighet; Air Pollution; Luftförorening; Air Pollution, Indoor; Luftförorening, inomhus; Lung Diseases; Lungsjukdomar; Environmental Exposure; Miljöexponering; Tobacco Smoke Pollution; Tobaksröksförorening; Pollen; Pollen; Rhinitis; Snuva; Pets; Sällskapsdjur; Heredity; Ärftlighet; Hypersensitivity; Överkänslighet; HEALTH; HÄLSA; Respiratory Medicine and Allergy; Lungmedicin och allergi